Machado de Assis: correspondence and criticism. - Rocha, Carlos [UNESP] (Univ Estadual Paulista-unesp, 2015)
The reading of Machado de Assis's correspondence - compiled in five volumes and published between 2008 and 2015 by Academia Brasileira de Letras, under the presentation, coordination and orientation of Sergio Paulo Rouanet unveil to today's reader, among other subjects, some brief analyses of Machado about his contemporaries poetry, in which the Bruxo do Cosme Velho advises them about the importance of work and study to reach artistic formal improvement. As long as they are open letters, published in newspapers and periodicals of the time, and Machado shows in them his understanding about poetical labor to his correspondent interlocutor and to the potential public, these correspondences in some way helped to create his image as a respectable critic. Because of this, this article aimed to establish a relationship between the analyses present in this correspondence with the commentaries that criticism has been promoting about Assis's poetical labor. For this purpose, some texts of the author's critical fortune and his correspondence published in volume I (1860-1869) and II (1870-1889) of Rouanet's edition are analyzed, without a chronological approach, but one related to the search of elements that formulate the referred relationship.
Keywords: Machado de Assis; Correspondence; Formal refinement; Critic